2014
DOI: 10.1016/j.neuroimage.2014.07.058
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous fMRI–PET of the opioidergic pain system in human brain

Abstract: MRI and PET provide complementary information for studying brain function. While the potential use of simultaneous MRI/PET for clinical diagnostic and disease staging has been demonstrated recently; the biological relevance of concurrent functional MRI-PET brain imaging to dissect neurochemically distinct components of the blood oxygenation level dependent (BOLD) fMRI signal has not yet been shown. We obtained sixteen fMRI-PET data sets from eight healthy volunteers. Each subject participated in randomized ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 43 publications
2
54
0
Order By: Relevance
“…30 The only other pain studies we are aware of that employed PET and fMRI together were performed in healthy individuals and used the non-selective radioligand ([ 11 C]diprenorphine). 16; 64 Our study is also the first to perform a whole brain search specifically correlating fMRI BOLD responses to pain with resting MOR BP. Our findings suggest that the dysregulation of the endogenous opioid system we previously reported in these FM patients is strongly related to an objective neural marker of their pain sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…30 The only other pain studies we are aware of that employed PET and fMRI together were performed in healthy individuals and used the non-selective radioligand ([ 11 C]diprenorphine). 16; 64 Our study is also the first to perform a whole brain search specifically correlating fMRI BOLD responses to pain with resting MOR BP. Our findings suggest that the dysregulation of the endogenous opioid system we previously reported in these FM patients is strongly related to an objective neural marker of their pain sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study 58 showed that pain relief could produce negative reinforcement through activation of the mesocorticolimbic reward-valuation circuitry. A recent human fMRI-PET study 59 found that increased endogenous opioid releases were at nucleus accumbens during pressure pain. Taken together, our results suggest that the cognitive control network, reward system, and descending pain modulatory network may all be involved in the modulation process of acupuncture treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a study that investigated pain modulation, simultaneously co-localized fMRI and PET signal changes with the opioid-ligand [ 11 C]diprenorphine were found in the thalamus and striatum. The positive correlation between thalamic changes in binding potential and magnitude of BOLD signal change suggests that pain-induced changes in opioid receptor binding directly contributes to the fMRI signal change in this region 90 . Other studies have investigated sequentially obtained PET receptor availability and fMRI signal in the same subjects: In the context of the opioid receptor system, BOLD response patterns due to watching movie clips of painful situations were shown to be correlated with μ-opioid receptor availability, as measured with [ 11 C]carfentanil, but not with D2 receptor availability, as measured with [ 11 C]raclopride 109 , suggesting the involvement of the opioid system, but not the dopamine system in vicarious pain.…”
Section: Multi-modal Imaging Of Receptor Functional Dynamics Witmentioning
confidence: 99%
“…Thus, the postulated role of the opioid system in mediating the effects of amphetamine needs to be further investigated. To assess whether such pain-induced changes in opioid neurotransmission contribute a significant component of the blood oxygenation level dependent (BOLD) functional MRI signal, simultaneous PET/MRI has been performed using [ 11 C]diprenorphine and dynamic data acquisition 90 . This study showed co-localized responses in thalamus and striatum related to pain processing indicating a correlation between opioid release and functional hemodynamic activation during pain.…”
Section: Types Of Challenges That Modulate Neurotransmission and mentioning
confidence: 99%